HUBUNGAN PELIBATAN ORANG TUA DALAM PEMBERIAN ASUHAN KEPERAWATAN DENGAN KECEMASAN ANAK USIA TODDLER YANG DIRAWAT DI RUMAH SAKIT - Koba, Liane Sandy (Indonesian Journal of Nursing Health Science, 2016)
AbstractToddler period is one stage of development between the autonomy of the opponent embarrassed and hesitant. Conditions ill and received treatment in hospital is one of crisis for children. Toddler childs reaction to the hospitalization was due to separation anxiety. The separation between children and parents the psychological impact on children, because children need parents during hospitalization. Nursing care is done to children undergoing treatment in hospitals require parental involvement (Platt, 1959 in Farrell, 1992). The purpose of this study was to determine the relationship between parent involvement in the provision of nursing care to the childs anxiety toddler who underwent treatment at the hospital. research methods is a cross-sectional sample of 35 patients with a number of children aged 1-3 years. Analysis of data transactions are carried out with chi square test. The results showed that there was an association between parental involvement in the provision of nursing care with anxiety toddler age children who are undergoing treatment at the hospital, with p = 0.349 in the value of Î± = 0.05 Keywords: the involvement of parents, toddler, nursing care, and anxiety